2022
DOI: 10.18632/aging.204245
|View full text |Cite
|
Sign up to set email alerts
|

Psoralen downregulates osteoarthritis chondrocyte inflammation via an estrogen-like effect and attenuates osteoarthritis

Abstract: Estrogen and its receptor play a positive role in the development of osteoarthritis (OA). Psoralen is a plantderived estrogen analog. This study aimed to verify whether psoralen inhibits OA through an estrogen-like effect. First, human primary chondrocytes in the late stage of OA were extracted to complete collagen type II immunofluorescence staining and cell proliferation experiments. Subsequently, estrogen, psoralen and estrogen receptor antagonists were co-cultured with OA chondrocytes, and RT-PCR was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Studies using animal models of a postmenopausal state and decreased estrogen level have indicated that maintaining a normal physiologic estrogen level can reduce OA symptoms [ 11 13 ]. Xu et el.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using animal models of a postmenopausal state and decreased estrogen level have indicated that maintaining a normal physiologic estrogen level can reduce OA symptoms [ 11 13 ]. Xu et el.…”
Section: Resultsmentioning
confidence: 99%
“…Psoralen is an estrogen analog that is derived from plants. Huang et al [ 13 ] studied the effects of psoralen in a rabbit OA model that was created by transection of the anterior cruciate ligament. The results showed that psoralen decreased the destruction of cartilage tissue reflected by Osteoarthritis Research Society International (OARSI) score and increased subchondral BMD, trabecular thickness and number.…”
Section: Resultsmentioning
confidence: 99%
“…Research indicates that psoralen exhibits a range of pharmacological activities, including anti-photoaging, anti-inflammatory, antioxidant, and immune regulation properties. [15][16][17] Due to its photosensitivity, psoralen combined with UVA photochemotherapy is an effective method for clinical treatment of psoriasis. Psoralen also has phototoxic and photocarcinogenic effects, it can insert into DNA and induce photochemical mutations, ultimately leading to cell damage, cell death, mutations, and even causing diseases such as skin cancer.…”
Section: Introductionmentioning
confidence: 99%